German women in Nazi thought (A historical study in the ideology of the Nazi party) - Kadhum Suhil, Athmar (International Journal of Psychosocial Rehabilitation, 2020)
Thanks to their oppressive organizations, the Nazis were able to fully control life in Germany, and their goal with this control was to form an ethnically pure society, completely subject to the control of the Nazi Party. And since the individual is the basis of society, they have set their sights on the life of the individual and the family since they came to power, and the matter began to impose strict control on the lives of the members of the Nazi party in order for the member to be raised. In his loyalty to the teachings of the Nazi PartyUnder this system, the family, especially women, occupied an important position as it was the pillar of the family, which is the nucleus of society. Therefore, the Nazi Party drew a new line for the life of women in the Third Reich, defining their position, role in society and relationship with men. All these issues mentioned are directly reflected in the research approach and its contents, which aims to trace the path of German women's rights and their position in German society, specifically during the era of Nazi rule:Review of the Nazi Party's ideology on women. What is its role in society and the tasks entrusted to it in preserving the Aryan race? And finally, its position in Nazi society